INFLUENCE OF THE ANTROPOMETRIC MEASURES OF THE ATHLETES THAT ARE PRACTICING THE VOLLEYBALL GAME ON TECHNICAL PROCEDURE SPIKE - Onesim Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In this scientific paper we highlighted the numerical importance of anthropometric parameters in the efficiency of the technical spike process. A series of anthropometric parameters were tested, and then we split and tested the yield obtained from the technical attack process. After final testing there was a direct proportional increase in the results obtained, so statistically the research was a success, P <0.05, 0.01.